Oceanic forcing of the global warming slowdown in multi-model simulations - Xu, Xinping; He, Shengping; Furevik, Tore; Gao, Yongqi; Wang, Huijun; Li, Fei; Ogawa, Fumiaki (International Journal of Climatology, 2020)
Abstract Concurrent with the slowdown of global warming during 2002–2013, the wintertime land surface air temperatures over Eurasia, North America, Africa, Australia, South America, and Greenland experienced notable cooling trends. The oceanic effects on the continental cooling trends are here investigated using two sets of uncoupled experiments with six different climate models. Daily and annually varying sea ice is prescribed for both sets of experiments, while daily and annually varying SST is used in the first set (EXP1) and daily and annually repeating climatological mean SST in the second set (EXP2). All six models capture the slowdown of global-mean land surface air temperature during 2002–2013 winters in EXP1 only. The slowdown concurs with a negative phase of the Pacific Decadal Oscillation (PDO), indicating that PDO plays an important role in modulating the global warming signal. Not all ensemble members capture the cooling trends over the continents, suggesting additional contribution from internal atmospheric variability. KEYWORDS continental cooling, global warming, multi-model simulations, Pacific Decadal Oscillation published version